Qadariyah, Jabariyah dan Ahlus Sunnah (Studi Komparatif Merespon Kebijakan Pemerintah dan Ulama Mencegah Merebaknya Covid-19) - Ronny Mahmuddin; Syandri, Syandri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study elaborated one phenomenon that occurs in Indonesia, particularly after the appeal issued by Indonesian Government and Indonesian Council of Ulama (MUI) for people to avoid crowded places including the mosques. People responses vary greatly so is with community leaders; of course, the response is the result of their understanding so far. This research used a descriptive qualitative method by using data related to theology that develops in Islam, namely Qadariyah, Jabariyah, and Ahlussunnah in particular in response to the policy of government and scholars on preventing the outbreak of Covid-19. The results of this study show that there are three groups who address the issue of destiny in different ways. First, Jabariyah is a group that only relies on Allah, but denies effort. Second, Qadariyyah, is a group that denies destiny, only does efforts but forget the reliance on God. Third is the middle group, Ahlu Al Sunnah wal Jamaah, which combine reliance with effort in matters of destiny. If it is analyzed carefully, among the three theological schools, the easiest one to support the maximization of government policy and the instructions of scholars in Indonesia is Ahlusunnah wal Jamaah. They combine belief in destiny with effort to maximize the achievement of the reliance process towards destiny.